(3OGFQI GdeYGQas (3bGehS YGe dcd af heWdH (B/s - (3GdHSJGfj, HWQS Hf HhdS Hf YHO Gddg,s 1234-1300 (3g`(B.s ((3HjQhJ (B:s (3OGQ GdeYQaI,s)
(3JJfGhd OGFQI GdeYGQa bGehS deYGfj GdcdeGJ aj TJi GdehGVjY, ef HjfgG GdUQa hGdfMh(B.s
(3eQJH JQJjH bGehSj(B.s
Keywords: (3OhGFQ GdeYGQa GdYQHjIs